Investigation of Reaction Rate of Bis(triethoxysilylpropyl)tetrasulphide in Silica-Filled Compound Using Pyrolysis-Gas Chromatography/Mass Spectrometry - Ha, Sung-Ho; Kim, Sung-Woo; Jeong, Ho-Kyun (Asian Journal of Chemistry, 2013)
Pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) was used to examine the reaction rate of bis(triethoxy-silylpropyl)tetrasulphide in silica-filled rubber. The major pyrolysis product of bis(triethoxysilylpropyl)tetrasulphide, which is used as a silane coupling agent, was found to be an allyltriethoxysilane. Allyltriethoxysilane was also detected in the uncured silica-filled styrene-butadiene rubber compound with bis(triethoxysilylpropyl)tetrasulphide. To investigate the silica/silane reaction rate, the allytriethoxysilane content was used as an indicator and quantified by the relative peak area ratio of allytriethoxysilane/styrene. Styrene is a pyrolysis product of styrene-butadiene rubber. The results revealed an increase in reaction rate with increasing allytriethoxysilane content. Overall, pyrolysis-gas chromatography/mass spectrometry can be used to estimate the reaction rate of the silica/silane system.